Land‐use influences phosphatase gene microdiversity in soils. (30th May 2017) - Neal, Andrew L.; Rossmann, Maike; Brearley, Charles; Akkari, Elsy; Guyomar, Cervin; Clark, Ian M.; Allen, Elisa; Hirsch, Penny R.
Summary: Phosphorus cycling exerts significant influence upon soil fertility and productivity – processes largely controlled by microbial activity. We adopted phenotypic and metagenomic approaches to investigate phosphatase genes within soils. Microbial communities in bare fallowed soil showed a marked capacity to utilise phytate for growth compared with arable or grassland soil communities. Bare fallowed soil contained lowest concentrations of orthophosphate. Analysis of metagenomes indicated phoA, phoD and phoX, and histidine acid and cysteine phytase genes were most abundant in grassland soil which contained the greatest amount of NaOH‐EDTA extractable orthophosphate. Beta‐propeller phytase genes were most abundant in bare fallowed soil. Phylogenetic analysis of metagenome sequences indicated the phenotypic shift observed in the capacity to mineralise phytate in bare fallow soil was accompanied by an increase in phoD, phoX and beta‐propeller phytase genes coding for exoenzymes. However, there was a remarkable degree of genetic similarity across the soils despite the differences in land‐use. Predicted extracellular ecotypes were distributed across a greater range of soil structure than predicted intracellular ecotypes, suggesting that microbial communities subject to the dual stresses of low nutrient availability and reduced access to organic material in bare fallowed soils rely upon the action of exoenzymes.